1995
DOI: 10.1088/0953-8984/7/5/006
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon scattering and anisotropy of conductivity in quasi-two-dimensional systems

Abstract: The inverse relaxation time tensor in quasi-two-dimensional systems is calculated for elastic electron scattering by both acoustic and optical phonons. It is shown that in the general case the relaxation time is anisotropic. Also, on the basis of the Boltzmann equation in the anisotropic relaxation time approximation the electrical conductivity in these systems is calculated. It is found that anisotropy of the conductivity is defined not only by the anisotropy of effective mass and the relaxation time but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The transverse thermopower, α ⊥ , as ε F > 2ε 0 (twodimensional case), obeys the next concentration dependence: where [9]. Formula (6) fits the experimental data in [10] where it was observed that the thermopower of the GaAs/Ga 1−x Al x As SLs is reduced by the elevated concentration.…”
Section: Longitudinal and Transverse Components Of The Thermoelectric...mentioning
confidence: 80%
See 2 more Smart Citations
“…The transverse thermopower, α ⊥ , as ε F > 2ε 0 (twodimensional case), obeys the next concentration dependence: where [9]. Formula (6) fits the experimental data in [10] where it was observed that the thermopower of the GaAs/Ga 1−x Al x As SLs is reduced by the elevated concentration.…”
Section: Longitudinal and Transverse Components Of The Thermoelectric...mentioning
confidence: 80%
“…From formulae (4) and ( 5) it transpires that on the impurity scattering the thermopower anisotropy (relation of the transverse component of the thermopower to the longitudinal one), in contradistinction to the anisotropy of the electrical conductivity [9], is merely dictated by the Fermi level to the mini-band width ratio and is irrespective of the effective mass anisotropy and superlattice constant.…”
Section: Longitudinal and Transverse Components Of The Thermoelectric...mentioning
confidence: 99%
See 1 more Smart Citation
“…Однако если рассеяние упругое, то межзонные процессы несущественны и можно ограничиться случаем, когда заполнена лишь одна мини-зона. Продольная и поперечная компоненты обратного времени релаксации при рассеянии на акустических (r = 0) и полярных оптических (r = 1) фононах пропорциональны плотности состояний g(ε) и имеют вид [20] 1…”
Section: общий вид гальванои термомагнитного тензоровunclassified
“…When calculating these components, it is presupposed that the scattering of conduction electrons is by acoustic phonons. The relaxation time at such types of scattering can be written as [7]:…”
Section: Hall Coefficientmentioning
confidence: 99%